The Role of Learning Motivation as a Mediating Variable in the Influence of Critical Thinking Ability on Income Statement Preparation Skills - Putri Nabilla Rasidi; Dassucik; Raudatul Jannah (Danadyaksa: Post Modern Economy Journal, 2026)
Critical thinking skills have been widely examined in relation to students' learning outcomes, particularly in learning activities that require analysis and problem-solving. This study aims to analyze the effect of critical thinking skills on income statement preparation skills and to examine the mediating role of learning motivation among eleventh-grade students in the Accounting specialization program. This study employed a quantitative approach using a survey method with an explanatory research design. The explanatory design was chosen because the study sought to explain the causal relationship between critical thinking skills and income statement preparation skills, with learning motivation serving as a mediating variable. The results of the partial test (t-test) indicated that the regression coefficient for income statement preparation skills increased by 0.861. The significance value obtained was less than 0.05 (Sig. < 0.001), indicating that critical thinking skills have a significant effect on income statement preparation skills. In Regression Model 1, critical thinking skills had a positive and significant effect on income statement preparation skills, contributing 67% of the explained variance. In Regression Model 2, the correlation coefficient (R = 0.015) indicated a very weak relationship between critical thinking skills and learning motivation. The coefficient of determination (R Square = 0.000) showed that critical thinking skills explained 0% of the variance in learning motivation. In other words, critical thinking skills had virtually no effect on learning motivation. In Regression Model 3, the model summary showed an R value of 0.821, indicating a very strong relationship between critical thinking skills and learning motivation in predicting income statement preparation skills. The R Square value of 0.674 indicated that 67.4% of the variance in income statement preparation skills was explained jointly by critical thinking skills and learning motivation, while the remaining 32.6% was attributable to other factors beyond the scope of this study.